Sustainable service - Volfson, Adi, 1971- (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
Service and the service dominant logic driving today's global economy influence every aspect of our lives, in the process, shaping our social and natural environments. This scenario dictates that new ways to provide services must be offered that will enrich service systems and service networks with added values and benefits, ultimately to yield sustainable services. To put sustainability into practice and generate sustainable services will require more than merely implementing efficient physical resource management in the production, delivery, and use of services. First and foremost, sustainable service is that which fulfills customer needs and can be perpetuated for long periods of time without negatively influencing the customer's natural or social environment. In addition, sustainable services should integrate smart use of nonphysical resources with environmentally and socially aware behaviour, and take into account the service's potential short- and long-term effects, on both the local and the global scales. As service systems and networks will undoubtedly become much more complex and specific in the future, they will require better coordination of the various actors, whether human or not, and better synchronization of the value production and delivery processes. These services should comprise three levels: (1) unidirectional value exchange from supplier to consumer, (2) bidirectional value co-creation between provider and customer, and (3) return of values by simultaneous co-generation of direct and indirect values by a provider and a customer to other customers (i.e., 3D services). Finally, the production of 3D services will enable the provision of long-term and indirect values and the co-creation of values with many indirect actors and even with the next generations. Moreover, sustainable services will be based on the generation of environmental, social, and economic values integrated into the provision of sustainability as a value, resembling the provision of ecosystem services.
1. The "evolution" of service and sustainability -- 2. Sustainability and service -- 3. Evaluating sustainable services -- 4. Physical resource assessment -- 5. Sustainability as a value -- 6. Trends in service science -- 7. From single service to whole service -- 8. What next? -- Index.
Includes bibliographical references (pages 123-132) and index.
Title from PDF title page (viewed on July 15, 2016).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Service industries; Sustainability; Customer services; Carbon footprint; CleanServ; Smart city; Service; Sustainability; Electronic books